One‐stage versus two‐stage technique using two splinted extra‐short implants: A multicentric split‐mouth study with a one‐year follow‐up. (14th June 2022) - Menini, Maria; Pesce, Paolo; Delucchi, Francesca; Ambrogio, Giulia; Canepa, Camilla; Carossa, Massimo; Pera, Francesco
Abstract: Objective: To compare the clinical outcomes of extra‐short implants (≤6.5 mm) inserted with one‐stage versus two‐stage technique in adjacent sites of the upper or lower jaw. Materials and Methods: In this split‐mouth multicenter study, implants were randomly divided into two groups according to the healing phase: two‐stage and one‐stage technique. Primary outcome measures were implant survival, implant success, and prosthodontic complications. Secondary outcome measurements were: implant stability quotient (ISQ) collected at surgery time (T0), and after 3 (T3) and 12 (T12) months, marginal bone level (MBL) evaluated at T0, T3, T6, and T12, marginal bone loss evaluated at T6 and T12, plaque index (PI), probing depth (PD), bleeding on probing (BoP) evaluated at T3, T6, and T12. Significances of differences between groups were tested by linear mixed model with random intercept. Results: Nineteen patients ( 8 males and 11 females) were included. A total of 38 implants were inserted. At T12 implant cumulative survival and implant success rate were 100% in both groups. No statistically significant differences were recorded for any of the analyzed parameters between the two groups at any time point. ISQ values were similar at T0 (two‐stage: mean 67.53 ± SD 19.47; one‐stage: mean 66.53 ± 19.07 p = 0.8738) and increased in both groups at the 12‐month follow‐up appointment (two‐stage: 81.1 ± 7.04; one‐stage: 81.39 ± 0.9266). MBL values were similar in the two groups at any time point. At T12 marginal bone loss was 0.46 ± 0.41 (two‐stage) and 0.45 ± 0.38 (one‐stage) mm ( p = 0.9417), while mean PD was 2.7 ± 0.85 (two‐stage) and 2.69 ± 0.89 (one‐stage) mm. Conclusions: Within the limits of the present short‐term report, extra‐short implants demonstrated optimal clinical outcomes using the one‐stage technique, without statistically significant differences compared with the traditional two‐stage approach.